Development of Digital Education in Libya: Progress, Challenges, and Future Directions - Yahya, Najeeb; Abdullah, Mahmoud; Masuwd, Mowafg (Lafadz Jaya Publisher, 2025)
This article examines the development of digital education in Libya, focusing on the integration of digital technologies within the educational system and their impact on teaching and learning processes. Over the last decade, Libya has made significant strides in embracing digital tools, yet the full potential of digital education remains untapped due to various challenges. These include limited infrastructure, inadequate training programs for educators, and socio-political instability. Despite these challenges, the Libyan government and higher educational institutions have invested in ICT infrastructure and e-learning platforms, aiming to bridge the digital divide. This article reviews the current state of digital education in Libya, highlights the hurdles faced, and explores strategies for the effective implementation of e-learning systems. It also offers insights into the future prospects of digital education in Libya, with a particular focus on the higher education sector. The findings suggest that a concerted effort from policymakers, educators, and international partners is crucial to overcome existing barriers and ensure the sustainable development of digital education in the country.